(untitled) (SCIÉNDO INGENIUM, 2024)
In this thesis, the design of a waste management manual is proposed, applying the standard guidelines of the Pmbok Sixth Edition, taking the Central Market of Trujillo as a case study. Given the lack of intervention of the actors involved, the little control, and little awareness in relation to the management of waste management in this establishment, it was considered pertinent to contemplate a project proposal that minimizes the threats that the current one represents for the environment inadequate management of solid waste in said market. In addition, it is considered that this applied research will serve as a background for future research that needs to improve solid waste management in supply centers, and that requires providing a solution to the problem generated by incorrect waste management; in this way, the project constitutes a pilot plan that could be applied in similar facilities throughout the region.